MERANGSANG KREATIVITAS MENGAJAR: DINAMIKA IKLIM ORGANISASI DAN PENGEMBANGAN KARIR PENDIDIK - Mulyoto Mulyoto; Erni Ayda (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2026)
21st-century education requires teachers to be highly creative. There is evidence that educators often lack creativity in their teaching. So, the right formula is needed to increase teacher creativity. This research aims to analyze the influence of the school's organizational climate on the creativity of educators in teaching, with management and career planning as the mediator variable. This research method uses quantitative approaches and data analysis techniques using Structural Equation Modelling (SEM) with the help of Smart-Pls version 4. The population of this study consists of certified Polri educators, with a total sample of 238 respondents. The results of the research show that the school's organizational climate has a positive and significant influence on the creativity of educators in teaching mediated by the career management and career planning of educator Indonesian National Police. This research provides a more holistic understanding of the relationship between the school's organizational climate, career development, and educators' creativity in teaching. These findings can serve as a foundation for developing more effective and sustainable education policies to increase educators' creativity to impact the quality of education in Polri educational institutions and other educational institutions.